2015
DOI: 10.1007/s12524-015-0462-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Above Ground Biomass for Central Indian Deciduous Forests Using ALOS PALSAR L-Band Data

Abstract: Reliable and accurate estimates of tropical forest above ground biomass (AGB) are important to reduce uncertainties in carbon budgeting. In the present study we estimated AGB of central Indian deciduous forests of Madhya Pradesh (M.P.) state, India, using Advanced Land Observing Satellite -Phased Array type L-band Synthetic Aperture Radar (ALOS-PALSAR) L-band data of year 2010 in conjunction with field based AGB estimates using empirical models. Digital numbers of gridded 1×1°dual polarization (HH & HV) PALSAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 52 publications
0
12
2
Order By: Relevance
“…However our results, also according to Figure 4, do not clearly show the usual 100-150 Mg/ha saturation limit reported in literature [1,57,58]; and it is difficult to understand if at higher AGB levels there is a scarce saturation effect or increased error in model. These results from a single research might be caused also by environmental characteristics of the study areas (e.g., soil and forest structure).…”
Section: Discussioncontrasting
confidence: 95%
“…However our results, also according to Figure 4, do not clearly show the usual 100-150 Mg/ha saturation limit reported in literature [1,57,58]; and it is difficult to understand if at higher AGB levels there is a scarce saturation effect or increased error in model. These results from a single research might be caused also by environmental characteristics of the study areas (e.g., soil and forest structure).…”
Section: Discussioncontrasting
confidence: 95%
“…AGB predicted in this study area was 72.54 Mg/ha. The estimates of AGB given in the current study are higher than the estimates calculated from deciduous forests in India (58 Mg/ha) [54] (Table 6). It also almost doubles compared to the value from Mediterranean forests in Italy (38 Mg/ha) [53] and the AGB value from boreal forests in Alaska (39.5 Mg/ha) [55].…”
Section: Discussioncontrasting
confidence: 83%
“…It also almost doubles compared to the value from Mediterranean forests in Italy (38 Mg/ha) [53] and the AGB value from boreal forests in Alaska (39.5 Mg/ha) [55]. However, the current AGB is lower than the biomass of mangrove forests in Thailand (250.53 Mg/ha) [52], tropical forests in Borneo (382 Mg/ha) [51], and conifer broadleaf forests in China (106.45 Mg/ha) [54]. The AGB of tropical forests is higher than that of private forests because natural forests store a large amount of biomass on terrestrial ecosystems which accumulates over a long period of time.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Wiseman et al reported that RADARSAT-2 polarimetric C-Band SAR HV can discriminate the level of biomass for canola and alfalfa crops [6]. Furthermore, C-band data, Advanced Land Observing Satellite-Phased Array type L-band Synthetic Aperture Radar (ALOS-PALSAR) cross-polarized HV backscatter information also showed a better relationship with the above-ground biomass of different forest types than co-polarized HH did [24]. A possible reason for this may be that the cross-polarized data (HV or VH) mainly originate from multiple scattering within the canopy and are less influenced by the canopy surface condition [25].…”
Section: Discussionmentioning
confidence: 99%